An evaluation of the health literacy of adult Pilipinos in a Barangay in Metro Manila, Philippines using the 2009 influenza a (H1N1) virus printed educational material - Espiritu-Ioan, Elinore
Health literacy is an all-encompassing human attribute that is essential for every individual to be able to read, process, understand, communicate, and apply health messages for health promotion, disease prevention, and health maintenance. In the absence of literature on health literacy in the Philippines, the objectives of this study were to estimate the reading and health literacy of 200 adult Pilipinos in Barangay in Metropolitan Manila, and examine their responses to the 2009 Influenza A (H1N1) Flu virus printed educational materials (PEM). The tests in this study included the REALM-SF, the STOFHLA Self-Report Survey, a Participant Feedback Survey, and a newly developed H1N1 Knowledge Test. A posttest only randomized design involved assigning participants to receive or not receive the N1H1 printed educational materials and then assessing knowledge levels in both groups. Results showed that, compared with participants who did not receive the educational materials, participants who received the H1N1 PEM had slightly higher levels of knowledge. While the differences were statistically significant, they were relatively small from a practical perspective. The finding indicated that while knowledge levels were generally high for most areas assessed, some topics were not well understood by the majority of participants. These included the potential virulence of the virus and the availability of effective treatment medication. The majority of participants also had misconceptions about certain modes of transmission, including consumption of pork and chicken. These data point to topics that may require particular attention in future public health education efforts. Feedback on the PEM was mostly positive, but participants offered a variety of recommendations for improvement, including adapting the language to local dialects and improving accessibility by increasing the font size of text, adding illustrations, and simplifying the language and eliminating or reducing technical medical “jargon.” This study can help guide future public health education endeavors in the country.